Test Tube Babies and Artificial Insemination - Riduan Hamid Lubis; Ghoiril Amri (ISNU Sumatera Utara, 2025)
The development of artificial reproductive technologies such as in vitro fertilization (IVF) and artificial insemination (AI) has had a significant impact on the medical world, particularly in helping couples experiencing infertility. In Indonesia, these practices not only have medical implications but also touch on ethical, legal, and religious issues. This study aims to comprehensively examine the implementation of IVF and AI from three main perspectives: medical, ethical, and legal. The research method used is a qualitative approach with a literature review and semi-structured interviews with medical personnel and legal experts. The results show that although medically these two technologies offer new hope for infertile couples, there are still pros and cons from an ethical and legal perspective, particularly regarding the status of children, the legitimacy of biological relationships, and the limitations of implementation according to applicable legal and religious norms in Indonesia. This research is expected to contribute to the formulation of more comprehensive regulations that support reproductive justice.